A Good article or not: Key Elements for an Impactful Scientific paper - Yusuf, Maryam M.B; Kasim, Suleiman I; Hussain, Mukhtar Ali; Ago, Amina Usman Sabo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose—This article is an essential guide for early career researchers embarking on writing and publishing scientific manuscripts in high-impact academic journals. Design/methodology/approach – Acknowledging the critical role of publication in building a researcher's academic reputation, the paper provides detailed guidance on crafting the first scientific manuscript. It addresses the common pitfalls and challenges associated with the process, particularly for novice writers unfamiliar with scientific papers' stringent structure and functional complexities. Findings – The manuscript is structured to demystify each component of a scientific paper, including the title, abstract, introduction, methods, results, discussion, conclusion, acknowledgments, and references. Through an observational approach, the paper highlights the most common mistakes made by new authors, such as issues with clarity, organization, citation errors, and non-compliance with journal guidelines. Additionally, it offers practical tips and strategies to avoid these pitfalls, emphasizing the importance of a clear narrative, thorough literature review, accurate data presentation, and adherence to ethical standards. Originality/value –The unique feature of this article is its concise, point-by-point guidance complemented by illustrative examples, making it an invaluable resource for early career researchers aiming to navigate the complexities of scientific manuscript preparation and achieve successful publication in prestigious academic journals.